Understanding public policy - Dye, Thomas R. (Boston, Massachusetts : Pearson, 2013)
Updated it its 14th edition, Understanding Public Policy focuses on the policy challenges confronting the Obama administration. This edition provides students with a close up look at the American healthcare system, current economic policies, issues of homeland security and defense policy among many other current event and issues shaping public policy today. The gold-standard for introductory public policy texts, Understanding Public Policy is designed to provide readers with concrete tools for both understanding and analyzing public policy.
1. Policy Analysis: What Governments Do, Why They Do It, and What Difference it Makes -- 2. Models of Politics: Some Help in Thinking About Public Policy -- 3. The Policymaking Process: Decision-Making Activities -- 4. Policy Evaluation: Finding Out What Happens After a Law Is Passed -- 5. Federalism and State Policies: Institutional Arrangements and Policy Variations -- 6. Criminal Justice: Rationality and Irrationality in Public Policy -- 7. Health Care: Attempting A Rational-Comprehensive Transformation -- 8. Education: Group Struggles -- 9. Economic Policy: Challenging Incrementalism -- 10. International Trade and Immigration: Elite-Mass Conflict -- 11. Energy and the Environment: Externalities and Interests -- 12. Civil Rights: Elite and Mass Interaction -- 13. Defense Policy: Strategies for Serious Games.
Includes bibliographical references and index.
Keywords: POLITICAL SCIENCE